(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article examines the regional cooperation of the Kyrgyz Republic in the field of migration policy using the example of the CIS, the Eurasian Economic Union (EAEU) and the countries of Central Asia. The article analyzes current trends, challenges and prospects for the development of cooperation between the states of the region in regulating migration flows, protecting the rights of migrants and countering illegal migration. Special attention is paid to the regulatory framework, institutional mechanisms and practical aspects of coordinating migration policy within the framework of these integration associations and regional groupings. The importance of strengthening cooperation to ensure sustainable socio-economic development, security and integration processes in the region is noted. The article highlights the need for further harmonization of migration legislation, improved information exchange, and the development of joint migrant support programs.